The United Nations against women: between ignorance and arrogance (Regarding the elaboration of a new Criminal Code for Honduras and proposals made by several UN offices on gender-based violence and abortion) - Álvarez García, Francisco Javier (EUNOMÍA. Revista en Cultura de la Legalidad, 2018)
Abstract: The author exposes the vicissitudes in the drafting of the new Honduras Criminal Code, particularly in reference to gender violence and abortion, and specially emphasizes how the unfortunate intervention of the officials of the United Nations High Commissioner and UN-Women, who lack sufficient training in the subject but plenty of arrogance, has prevented Honduras the adoption of progressive and adequate legislation in these matters
Keywords: Keywords: United Nations, Honduras, abortion, gender violence, arrogance, ignorance, femicides, Criminal Code, United Nations High Commissioner, UN-Women, OHCHR, National Congress of Honduras.; United Nations; Honduras; abortion; gender violence; ignorance; femicides; Criminal Code; United Nations High Commmissioner; UN-Women; OHCHR; National Congress of Honduras